Development of a Novel Controlled-Release Tablet of Pregabalin: Formulation Variation and Pharmacokinetics in Dogs and Humans - Kim KH; Lim SH; Shim CR; Park J; Song WH; Kwon MC; Lee JH; Park JS; Choi HG (Dove Medical Press, 2020)
Kyung Hun Kim,1,2 Seo Hyun Lim,2 Cho Rok Shim,2 Junsung Park,2 Woo Heon Song,2 Min Chang Kwon,2 Jong Hyuk Lee,3 Jun Sang Park,2 Han-Gon Choi1 1College of Pharmacy and Institute of Pharmaceutical Science and Technology, Hanyang University, Ansan, Republic of Korea; 2GL PharmTech Corp, Seongnam, Republic of Korea; 3Department of Pharmaceutical Engineering, College of Life and Health Sciences, Hoseo University, Asan, Republic of KoreaCorrespondence: Jun Sang ParkGL PharmTech Corp, #714, Jungang Induspia V, 137 #714, Jungang Induspia V, 137, Seongnam-Si, Gyeonggi-Do 13202, South KoreaTel +82-31-739-5220Fax +82-31-739-5224Email jspark@glpt.co.krHan-Gon ChoiCollege of Pharmacy and Institute of Pharmaceutical Science and Technology, Hanyang University, Ansan, Republic of KoreaEmail hangon@hanyang.ac.krBackground: Novel three-layered (TL) tablet systems were compared with both monolithic matrix (MM) formulations and a commercial immediate-release (IR) capsule to develop once-a-day (OAD) pregabalin tablets.Methods: The physical properties of the TL tablets, including dissolution and swelling rates, were compared with those of the MM tablets and the pharmacokinetic parameters of the TL tablet were compared with those of an IR capsule in beagles and humans.Results: Our results indicated that the same amount of a hydrophilic polymer in the formulations had similar dissolution profiles at 12 h, regardless of the tablet geometry. However, the degree of tablet swelling differed, with larger amounts of polymer in the tablets showing a greater degree of swelling. In addition, TL tablets swelled more rapidly compared with MM tablets. For the pharmacokinetic study of the TL tablet, the beagles demonstrated absorption results similar to those of an IR capsule, whereas the humans demonstrated low total absorption compared with an IR capsule. The time of the peak plasma concentration at 6 h in the fed state of humans coincided with the results of the study on beagles.Conclusion: The novel TL tablet system of pregabalin may prove to be helpful in developing improved formulations with better continuous drug absorption for OAD administration.Keywords: controlled-release, three-layered tablet, polyethylene oxide, high swellable, once-a-day